7 I just took the test! Hope this helped
Answer:
12x + 18y + 6z + 4x - 4z
Step-by-step explanation:
Given the expression : 3(4x + 6y + 2z) + 4(x – z)
To eliminate the parenthesis ; we use the distributive property :
3(4x + 6y + 2z) + 4(x – z) becomes ;
3*4x + 3*6y + 3*2z + 4*x + 4*-z
12x + 18y + 6z + 4x - 4z
Hence,
12x + 4x + 18y + 6z - 4z
16x + 18y + 2z
Y - y1 = m(x - x1)
slope(m) = -1/2
(-4,-2)...x1 = -4 and y1 = -2
now we sub
y - (-2) = -1/2(x - (-4) =
y + 2 = -1/2(x + 4) <=====
Answer:
-3/4
Step-by-step explanation:
change them to improper fractions
-5/2 - (-7/4)
now multiply -5/2 by two so the denominators are the same
-10/4 - (-7/4)
subtracting a negative number is the same as adding a positive number
-10/4 + 7/4
= -3/4
We have
3 / (x-5) - x/5
We make the GCF and we have
15/[ 5(x-5) ] - x(x-5)/[ 5(x-5)]
= [ 15 - x(x-5) ] [5(x-5)]
= [ 15 - x^2 + 5x] / [ 5 (x-5) ]
= [15 - x^2 + 5x]/[5x - 25]
An answer to your question is (15-x^2+5x)/(5x-25)